Peningkatan Keterampilan Menulis Teks Narasi Menggunakan Model Circuit Learning di Kelas IV SDN 20 Indarung Kota Padang - Fauzia. Z, Sri; Suriani, Ari; Chandra , Chandra; Muhammadi , Muhammadi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to describe the improvement of writing skills of students using the Circuit Learning model in the fourth grade at SDN 20 Indarung, Padang City. The approach used is both qualitative and quantitative. The subjects of this research are the teacher and 30 fourth-grade students. This type of research is a Classroom Action Research (CAR) conducted in two cycles, where Cycle I consists of 2 meetings and Cycle II consists of 1 meeting. Each cycle includes four stages: planning, implementation, observation, and reflection. Data collection techniques include observation, tests, non-tests, and document analysis. The research results show an improvement, with cycle I starting with an analysis of preparation results: a) The teaching module showed an average of 85 (B) and in cycle II increased to 95 (A), b) The implementation of the teacher aspect in cycle I had an average of 85.94 (B) and in cycle II an average of 91.7 (A), while the implementation of the student aspect in cycle I had an average of 85.94 (B) and in cycle II became 91.7, c) The assessment of students' writing skills in narrative texts in cycle I had an average of 75.55 (C) and in cycle II an average of 84.61 (B). Based on these results, it can be concluded that the Circuit Learning model can improve students' writing skills in narrative texts in the fourth grade at SDN 20 Indarung, Padang City.